Facile one-step synthesis of Fe5(PO4)4(OH)3 · 2H2O hollow octahedra and their application for DNA separation. (18th August 2018) - Hao, Xiaoyun; Li, Shanzhong; Zhang, Dongen; Gong, Junyan; Ren, Lizhen; Ma, Juanjuan; Tong, Zhiwei
ABSTRACT: A simple one-step process has been used to synthesize novel Fe5 (PO4 )4 (OH)3  · 2H2 O hollow octahedra in a mixed solvent of diethylene glycol (DEG) and H2 O. The x- 1 ray diffraction (XRD) and scanning electron microscopy (SEM) have been provided for the characterizations of the nanostructures. The shape of the as-obtained products could be controlled by adjusting the volume ratio of DEG and H2 O in the solvothermal process. The possible formation mechanism was proposed based 2 on nucleation and the Ostwald ripening process as well as the soft-template function of DEG. In addition, the study herein demonstrated that the hollow octahedra exhibit excellent capability for the adsorption of salmon sperm DNA and would have great application potentials in DNA separation.